Date: Jan 20, 2001 9:04 PM
Subject: Re: FLT Discussion: Simplifying
<firstname.lastname@example.org> wrote in message news://email@example.com...
> Let's say that I'm in some other ring besides integers. All the
> results I've given are still true. That is,
> (x+sqrt(-1)y)(x-sqrt(-1)y) = x^2 + y^2, and if x^2 + y^2 = 0, then
> (x+sqrt(-1)y)(x-sqrt(-1)y) = 0.
> You've all been insisting that I have to know what ring x and y are in
> to prove whether or not this means that
> (x+sqrt(-1)y) = 0 *or* (x-sqrt(-1)y) = 0.
1. What is x and y?
2. What is sqrt(-1) exactly?
3. How are the operations (+,*) defined?
4. In what ring (if any) are (x + sqrt(-1)y) and (x - sqrt(-1)) in?